2011
DOI: 10.4315/0362-028x.jfp-11-148
|View full text |Cite
|
Sign up to set email alerts
|

Geographical and Annual Variation in Lipophilic Shellfish Toxins from Oysters and Mussels along the South Coast of Korea

Abstract: To better understand critical aspects of diarrhetic shellfish poisoning (DSP) occurrence in a chief producing region of bivalves in Korea, the geographical and annual variation of DSP toxins and other lipophilic toxins in mussels (Mytilus galloprovincialis) and oysters (Crassostrea gigas) were investigated by liquid chromatography-tandem mass spectrometry in an area on the south coast of Korea from 2007 to 2009. The total lipophilic shellfish toxin (LST) levels in bivalves showed geographical and annual varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…In previous studies, we detected only low concentrations of lipophilic toxins in bivalves such as oysters (Crassostrea gigas) and mussels (Mytilus galloprovincialis) from the southern coast of Korea, but we found significant seasonal variation with peaks of toxicity in spring and summer (13, 19). Thus, the coast of Korea (13,19), the lack of PTX2 detection in this study is an interesting result. PTX2 may be rapidly converted into one of its derivative acids in gastropods, as has been shown in bivalves (29,30).…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…In previous studies, we detected only low concentrations of lipophilic toxins in bivalves such as oysters (Crassostrea gigas) and mussels (Mytilus galloprovincialis) from the southern coast of Korea, but we found significant seasonal variation with peaks of toxicity in spring and summer (13, 19). Thus, the coast of Korea (13,19), the lack of PTX2 detection in this study is an interesting result. PTX2 may be rapidly converted into one of its derivative acids in gastropods, as has been shown in bivalves (29,30).…”
Section: Discussionmentioning
confidence: 74%
“…The concentrations of lipophilic toxins in gastropod tissues were lower than the regulatory safety limits of the EU. In previous studies, Korean bivalves were also found to contain lipophilic toxins in concentrations below the regulatory limit (13,15,19). Korean gastropods can apparently be deemed safe for human consumption considering DSP toxin contents.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…(15) also reported that K orea ranked 3rd (292,405 tons) and 14th (135,720 tons) in the world for the production o f cephalopods and crustaceans, respectively, in 2012. These products are exported mainly to the U nited States, China, Japan, and the E uropean U nion (EU) (27). the aquatic environm ent and increase the contam inant load for hum ans consum ing these organism s (10,32,38).…”
mentioning
confidence: 99%